RANCANG BANGUN APLIKASI MANAJEMEN REGISTRASI DAN GATE CHECK BERBASIS WEB - Ilham, Muhammad; Anshori, Iedam Fardian (Universitas Majalengka, 2024)
In the digital era, organizing large-scale events requires maximum efficiency and effectiveness. This research focuses on designing and implementing a web-based registration and gate check management application to support these processes. Utilizing the Laravel framework, this application aims to enhance administrative efficiency and participant experience. A holistic approach, considering both technical aspects and user experience, is applied to optimize the application's workflow. A structured development methodology and rigorous testing are employed to ensure optimal application performance. It is hoped that this application will significantly contribute to the organization of large-scale events. By streamlining the registration and gate check processes, the application aims to reduce administrative burdens and improve participant satisfaction. With careful attention to technical and user aspects, this application aims to provide a smooth and efficient experience for event organizers and participants alike.